QUALITY ASPECTS: a perspective based on the percentage of items in its composition - Sanches, Larissa Ellen; de Souza Junior, Marco Antonio Alves (Revista Interface Tecnológica, 2020)
To Manufacture a good product is becoming a challenge in a world where people are increasingly demanding. This presupposes that producers are gradually investing in their production. In the production process of ice cream there are several factors that compromise the quality of the final product, and for this not to occur is necessary a good selection of raw material, balance and storage correct and follow some steps of production. This article aims to describe what the parameters for ice cream to have quality according to color, aroma, texture, body and flavor and the factors that interfere with the quality of it, among them the balance and incorrect storage. The development was done with a theoretical-conceptual research called bibliography. After the survey of data, it can be observed that each ingredient put in the wrong proportion or be stored incorrectly, can negatively affect any of the quality parameters.